Towards an Understanding of the Social Aspects of Sustainability in Product Design: Teaching HE students in the UK and Ireland through reflection and peer learning - Watkins, Matthew (Design and Technology Education: An International Journal, 2014)
This paper presents findings from a doctoral study, which investigated effective methods for teaching social sustainability within product design courses in British and Irish universities. This paper explores approaches for encouraging students to explore the social aspects of sustainable product design through workshops specifically designed to foster deep learning through collaboration,discovery and critical reflection.The importance of deep learning is reflected in both the sustainable design education (O’Rafferty et al., 2008, Griffith and Bamford, 2007) and education for sustainability literature (Warburton, 2003) as important to an understanding of the holistic and complex nature of sustainability.Three 'Rethinking Design' workshops were designed and developed as part of the doctoral main study to introduce students to the wider social aspects of sustainability and these were conducted in five universities in Britain and Ireland. The workshops were developed to foster principles that encourage students to adopt deep learning methods, taking into account the specific learning preferences of the current generation of students to enhance motivational factors such as relevance, appropriate teaching materialsand opportunities for collaborative learning. The workshops were tested amongst 150 undergraduate and postgraduate students and found to be successful in fostering deep learning by facilitating learning through discovery, critical reflection, peer learning and creativity leading to an exploration of design thinking solutions.